Analisis Kesenjangan Penerapan Manajemen Keselamatan pada Wisata River Tubing di Sungai Cileat, Subang - Revi Agustin Aisyianita; Silvia; Arif Setyo Nugroho; Muhammad Dafa Anggana; Daffa Ramadhan Argiansyah; Udan Karyawan (Journal of Tourism and Economic, 2026)
This study examines the gap between ideal standards and actual practices in the implementation of safety management in river tubing activities at Cileat River, Subang. A qualitative approach was employed through observations, interviews, and documentation involving key stakeholders. The findings indicate that safety practices remain operational and experience-based rather than systematically institutionalized. Critical gaps are identified in the absence of formal standard operating procedures (SOPs), lack of certified guides, weak risk management systems, and limited safety education for tourists. These conditions reflect a structural gap in safety governance, leading to suboptimal service assurance. This study highlights the necessity of shifting from experience-based practices toward a standardized, integrated, and sustainable safety management system as a prerequisite for enhancing service quality in adventure tourism.